A Comparative Analysis Opinion Mining Sea Games On Social Media - Lathifatuz zuhroh; Nuryana, I Kadek Dwi (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2025)
Twitter is a social media platform that is freely accessible to everyone. As a result, numerous social phenomena and issues quickly emerge and spread globally through users' tweets. The 2023 SEA Games in Cambodia was no exception, as it sparked public opinion, particularly among Indonesian citizens, due to several incidents during the event that were considered unethical or inappropriate. This study aims to analyze public sentiment regarding these events using the C5.0 and Naïve Bayes algorithms. The performance of both algorithms will be compared to determine which one yields better results. The dataset consists of 1,000 tweets collected between March 14 and April 14, 2023. The findings indicate that Naïve Bayes outperforms C5.0, achieving an accuracy of 70%, compared to 67% for C5.0 . Keyword: Twitter, Sentiment Analysis, Naïve Bayes, C5.0, Sea Games.